2009
DOI: 10.1007/s11207-009-9387-9
|View full text |Cite
|
Sign up to set email alerts
|

The Ulysses Catalog of Solar Hard X-Ray Flares

Abstract: Ulysses was launched in October 1990, and its Solar X-ray/Cosmic Gamma-Ray Burst Experiment (GRB) has provided more than 13 years of uninterrupted observations of solar X-ray flare activity. Due to the large variation of the relative solar latitude and longitude of the spacecraft orbit with respect to the Earth, the perspective of the GRB instrument often differed significantly from that of X-ray instruments on Earth-orbiting satellites. During extended periods the GRB experiment made direct observations of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Brodrick et al (2005) analyzed SIDs for this flare to deduce peak SXR classifications of X45 ± 5 (from sudden phase anomalies of VLF transmissions) and X34-X48 (from sudden HF cosmic noise absorption measured by riometers), respectively. From a comparison of GOES 1-8 Å and Ulysses >25 keV peak X-ray fluxes, Tranquille et al (2009) deduced a SXR flare classification of 24.8 ± 12.6, consistent with the X30.6 determination of Kiplinger & Garcia (2004). We take a mean value of X35 from the~X25-45 range of estimates for the 4 November 2003 flare and assign an uncertainty of ±5 classification units, weighting the more direct assessment of Kiplinger & Garcia (2004) higher than the SID-based estimates of Thomson et al and Brodrick et al Boteler (2006) noted that the SFE recorded at 11:15 local time for the 4 November flare at Victoria Magnetic Observatory in British Columbia (for which the geographic latitude of 48.5°N is similar to the 51.5°N latitude of London) was 100 nT (DH) compared with the 110 nT recorded at Kew (cf., Clarke et al 2010) In another approach to determine the size of the largest possible solar flare, Schrijver et al (2012) and Aulanier et al (2013) determined the peak attainable bolometric energy based on the observed maximum areas and magnetic field strengths of solar active regions and an estimated magnetic energy conversion efficiency.…”
Section: à2supporting
confidence: 77%
See 1 more Smart Citation
“…Brodrick et al (2005) analyzed SIDs for this flare to deduce peak SXR classifications of X45 ± 5 (from sudden phase anomalies of VLF transmissions) and X34-X48 (from sudden HF cosmic noise absorption measured by riometers), respectively. From a comparison of GOES 1-8 Å and Ulysses >25 keV peak X-ray fluxes, Tranquille et al (2009) deduced a SXR flare classification of 24.8 ± 12.6, consistent with the X30.6 determination of Kiplinger & Garcia (2004). We take a mean value of X35 from the~X25-45 range of estimates for the 4 November 2003 flare and assign an uncertainty of ±5 classification units, weighting the more direct assessment of Kiplinger & Garcia (2004) higher than the SID-based estimates of Thomson et al and Brodrick et al Boteler (2006) noted that the SFE recorded at 11:15 local time for the 4 November flare at Victoria Magnetic Observatory in British Columbia (for which the geographic latitude of 48.5°N is similar to the 51.5°N latitude of London) was 100 nT (DH) compared with the 110 nT recorded at Kew (cf., Clarke et al 2010) In another approach to determine the size of the largest possible solar flare, Schrijver et al (2012) and Aulanier et al (2013) determined the peak attainable bolometric energy based on the observed maximum areas and magnetic field strengths of solar active regions and an estimated magnetic energy conversion efficiency.…”
Section: à2supporting
confidence: 77%
“…The GOES 1-8 Å emission in this event saturated at an SXR classification of X17.4, but Kiplinger & Garcia (2004) used 3 s SXR data to reconstruct the light curve -making reference to those of other flares with similar time profiles from the same active region -to estimate a peak classification of X30.6. Thomson et al (2004Thomson et al ( , 2005 and 1 The 1 June 1991 event (Kane et al 1995;Tranquille et al 2009) may have been comparable in intensity. The measured (estimated) saturation time above the X17.4 level was~13 (~10) min for 4 November 2003 (1 June 1991).…”
Section: à2mentioning
confidence: 96%
“…Thus the total magnetically stored energy sets a firm upper limit on the magnitude of a flare, but the practical (and lower) limit would come from the properties of a "minimum current corona" of some kind (Longcope 1996). Either way the power-law distribution of flare energies must roll over around this maximum point, as suggested by observation (Kucera et al 1997;Tranquille et al 2009;Wheatland 2010) and statistical analysis (e.g. Kubo 2008).…”
Section: Interpretation Of the "Saturation" Correlationmentioning
confidence: 99%
“…Increasing interest in extreme Space Weather events for both practical and theoretical reasons has led to the re-examination of various aspects of the Carrington event, especially the flare size (Kiplinger & Garcia 2004;Tranquille et al 2009;Clarke et al 2010;Cliver & Dietrich 2013). As most of the mentioned studies agree, the Carrington flare may have been a large one, about the size of a X45-X50 solar flare.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Kiplinger & Garcia (2004) reconstructed the light curve to estimate a peak classification of X30.6. Thomson et al (2004Thomson et al ( , 2005 and Brodrick et al (2005) estimated an SXR classification of X45 ± 5 and X34-X48, respectively, but years later Tranquille et al (2009) deduced a flare classification of X24.8 ± 12.6.…”
Section: Introductionmentioning
confidence: 99%